Illness experience and coping styles of young and middle-aged patients with sudden sensorineural hearing loss: a qualitative study - Yang Yuan; Hong Wang; Qiuyun Chen; Congyan Xie; Haixia Li; Lu Lin; Li Tian (BMC, 2021)
Abstract Background The incidence of Sudden Sensorineural Hearing Loss (SSNHL) is increasing and tends to occur at a young age. The patient's disease experience during treatment is related to their physical and mental health. Effective coping styles such as proactively solving problems and asking for help will alleviate the patients' psychological symptoms and improve their quality of life. Aims and objectives To explore the illness experience and coping styles of young and middle-aged patients with SSNHL (age: 18-64 years), clarify the relationship between the two, and understand the psychological state and needs of the patients. Methods The purposive and maximum difference sampling method was used to conduct semi-structured interviews with 23 young and middle-aged SSNHL patients. The interview data were analyzed by Colaizzi's seven-step analysis. Results The illness experience of young and middle-aged SSNHL patients was complex, including symptoms during the onset of deafness and emotional experience before and after diagnosis. The coping styles of young and middle-aged SSNHL patients were active and diverse, including active acquisition of information, change in living habits, and seeking the care and attention of medical staff. Illness experience and coping style influence each other: good illness experience leads to active coping styles; active coping style results in good illness experience. Conclusions The illness experience of young and middle-aged SSNHL patients includes not only physical symptoms, but also changes in psychological and emotional reactions. Good illness experience can lead patients to adopt active coping style. Active and effective coping styles, such as positive acquisition of information, change in living habits and seeking care and help, can improve patients' illness experience.